HOW TO IMPROVE CREATIVE THINKING SKILL. - Mirzayeva F.N (TADQIQOTLAR.UZ, 2023)
ABSTRACT From your leisure time to your profession, creativity can fuel success and fulfillment in all facets of your life. However, how can you spark your creative inspiration? And why is honing one's capacity for creative thought so crucial? We'll look more closely at creativity and creative thinking in this post, both within and outside of the workplace. Continue reading to discover simple ways to infuse your life with greater creativity and the reasons it's such a worthwhile endeavor for your job and beyond.Describe creativity.Being creative is a vague term with a variety meanings, so depending on who you ask or where you look, you'll probably receive a different response. Examining the root word first is helpful as a starting point.